Textiles, identity and innovation : design the future : proceedings of the International Conference on Textiles, Identity and Innovation (D-TEX 2017), Lisbon, Portugal, 2-4 November 2017 /: design the future : proceedings of the International Conference on Textiles, Identity and Innovation (D-TEX 2017), Lisbon, Portugal, 2-4 November 2017. ([2019]) - Unknown
No abstract available